Evaluation of Factors Influencing Rock fragmentation by Blasting using Interrelations Diagram Method - Mulenga, Sunday (Journal of Physical Sciences, 2020)
Purpose: The purpose of this study is to develop an interrelations diagram for the factors affecting rock fragmentation by blasting and to determine their theoretical percentage contribution to rock fragmentation by blasting Methodology: In order to develop an interrelations diagram for factors affecting rock fragmentation by blasting, first, factors that affect rock fragmentation by blasting were identified through literature review. Secondly, uncontrollable factors whose influencing factors are difficult to pin point where group into three major categories of hardness factor, joints and in-situ block size. Thirdly, the cause and effect relationship between al factors affecting rock fragmentation were identified. The factors affecting rock fragmentation by blasting were then arranged in an orderly fashion and the arrows indicating the direction of influence were drawn among them. The arrows entering and leaving each factor were counted and count value for each factor was used to calculate the theoretical percentage contribution for each factor. Findings: Based on the Interrelations Diagram method, the top four influential controllable parameters towards rock fragmentation are Burden with 12%, Blasthole diameter with 9%, Powder factor with 7% and Delay timing with 7%. The most influential uncontrollable parameter towards rock fragmentation is Hardness Factor with 4%. It was further revealed that Controllable factors are more influential toward rock fragmentation by blasting than uncontrollable factors. This can be seen from the cumulative percentage contribution of 90% for controllable factors compared to cumulative percentage contribution of 10% for uncontrollable factors. Unique contribution to theory, practice and policy: Application of the interrelation diagram gives insight on how factors affecting rock fragmentation by blasting are generally interrelated and identifies the theoretical percentage contributions of factor towards influencing rock fragmentation by blasting